Holding Horizon: A New Measure of Active Investment Management - Chunhua Lan; Fabio Moneta; Russ Wermers (University of Cologne, Centre for Financial Research (CFR), 2018)
This paper proposes a new holding horizon (HH) measure of active management and examines the relation between horizon and manager skill. Our HH measure identifies, in the cross-section, funds with higher future long-term alphas, while reported turnover identifies, in the time-series, when a particular fund is likely to exhibit a higher short-run alpha. The superior long-term performance of long-horizon funds is due to their selection of stocks with strong long-run fundamentals. Moreover, stocks largely held by long-horizon funds outperform stocks largely held by short-horizon funds by 2.7% - 3.5% per year, adjusted for risk, over the following five-year period.
Keywords: G11; G23; 330; mutual funds; performance evaluation; investment horizons; selection skills